A Multifunctional Peptide‐Conjugated AIEgen for Efficient and Sequential Targeted Gene Delivery into the Nucleus. Issue 15 (8th March 2019) - Cheng, Yong; Sun, Chunli; Liu, Rui; Yang, Juliang; Dai, Jun; Zhai, Tianyou; Lou, Xiaoding; Xia, Fan
Abstract: Gene therapy has immense potential as a therapeutic approach to serious diseases. However, efficient delivery and real‐time tracking of gene therapeutic agents have not been solved well for successful gene‐based therapeutics. Herein we present a versatile gene‐delivery strategy for efficient and visualized delivery of therapeutic genes into the targeted nucleus. We developed an integrin‐targeted, cell‐permeable, and nucleocytoplasmic trafficking peptide‐conjugated AIEgen named TD NCP for the efficient and sequential targeted delivery of an antisense single‐stranded DNA oligonucleotide (ASO) and tracking of the delivery process into the nucleus. As compared with TD NCP/siRNA‐NPs (siRNA functions mainly in the cytoplasm), TD NCP/ASO‐NPs (ASO functions mainly in the nucleus) exhibited a better interference effect, which further indicates that TD NCP is a nucleus‐targeting vector. Moreover, TD NCP/ASO‐NPs showed a favorable tumor‐suppressive effect in vivo. Abstract : Tracking and delivery : A conjugate enabling the delivery of gene therapeutic agents to the nucleus of cancer cells and real‐time tracking was named TNCP for its four segments: a targeted peptide (ligand for the integrin αv β3 receptor), a nuclear localization signal, a cell‐penetrating peptide, and PyTPE, a molecule with AIE properties. Nanoparticles formed with an antisense oligonucleotide (ASO; see picture) targeted cancer cells and suppressed tumor growth.